CORRELATION OF PERIODONTAL STATUS WITH GLYCEMIC STATUS AND INSULIN RESISTANCE IN A SYSTEMICALLY HEALTHY SAUDI ARABIAN POPULATION – A PRELIMINARY REPORT (CAHIERS MAGELLANES-NS, 2024)
Introduction :It is unclear how periodontal status could affect glycemic status in people who are otherwise healthy. It has been suggested that patients with severe periodontitis have impaired glycemia and insulin resistance among those who were not previously diagnosed with diabetes mellitus. Our study aimed to compare the periodontal status with the parameters of insulin resistance and glycemic parameters in otherwise systemically healthy individuals.Materials and Methods: A cross‑sectional analytical design was employed where 339 systemically healthy individuals in the age group of 19–79 years were recruited for the study. Periodontal parameters measured included plaque index, bleeding index, probing depth and clinical attachment loss. Radiographs were used to assess bone loss. The fasting blood sugar (FBS), glycosylated hemoglobin (HbA1c), and BMI and waist circumference were measured to assess insulin resistance.Results: There were statistically significant differences between the mean Bleeding index, BMI, fasting, random blood glucose levels and Hba1c levels(P<0.05). The Multinomial Regression depicted that the odds between the Gingivitis and Healthy individuals were not statistically significant (p>0.05). Similarly, the odds of having periodontitis and variations in the glycemic parameters and BMI and waist circumference were also high.Conclusions: The mean FBS, HbA1c, BMI and Waist circumference were significantly higher in periodontitis patients than in the healthy and gingivitis group therefore early identification of abnormalities in systemic parameters based on the periodontal status is suggested.